Characterization of Biocompatible Poly(Ethylene Glycol)-Dimethacrylate Hydrogels for Tissue Engineering - Lopes, João (2019)
Tissue Engineering depends on broadly techniques to regenerate tissues and/or organ functions. To do so, tailored polymeric and/or hydrogel scaffolds may be used to ensure the appropriate regeneration. Hydrogels are suitable materials for constructing cell-laden matrices as they can be produced with incorporation of cells and rapidly cross-linked in situ through photopolymerisation reactions. Measurement of the polymerization degree, as well as resistance to compression and water retention are fundamental tests to evaluate the characteristics of hydrogels. In this work, free-radical polymerisation of poly(ethylene glycol)-dimethacrylate (PEGDMA) in UV light was assessed. Several hydrogels with different photoinitiator and water contents were produced to evaluate their influence on hydrogels behaviour. Experiments showed that variations on water and photoinitiator content induce changes in the physical and chemical behaviour of hydrogels. As it was found, water content prevents polymerisation to occur and reduces the mechanical properties of hydrogels weakening them. Furthermore, differences were found in varying water content from 15 to 30%, since this increase turned hydrogels more fragile and increase their stabilization time for water retention.